Study guides

☆☆

Q: If 4a plus b 12 then a?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

5ab-2ab+4a-b+5b = 3ab+4a+4b

a-b+a-b+2b+a = 4a

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

The expression is: (4a+b)/(2a-5b)

6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b

Related questions

5ab-2ab+4a-b+5b = 3ab+4a+4b

a+a+a+a+b+b - add the like terms =4a+2b 4a and 2b cannot be added because they are not like terms.

a-b+a-b+2b+a = 4a

It is an expression of two terms as: 4a+12

4a+3-a =12 4a-a = 12-3 3a = 9 a = 3

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

7a-2b

The expression is: (4a+b)/(2a-5b)

(a + 2 - b) (a + 2 + b)

1/4

It is 2a-b simplified

5

People also asked